2023
DOI: 10.1002/cncy.22690
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Diff‐Quik cytology smears for large‐panel mutation testing in lung cancer—Predicting DNA content and success with low‐malignant‐cellularity samples

Abstract: Background Cytology smears are commonly collected during endobronchial ultrasound–guided transbronchial needle aspiration (EBUS TBNA) procedures but are rarely used for molecular testing. Studies are needed to demonstrate their great potential, in particular for the prediction of malignant cell DNA content and for utility in molecular diagnostics using large gene panels. Methods A prospective study was performed on samples from 66 patients with malignant lymph nodes who underwent EBUS TBNA. All patients had ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Sequencing sensitivity was therefore compromised, with few somatic coding mutations being detected (9 versus 51) and used in TMB scores (5 versus 24) compared to its paired slide ( Table 1 ; Supplementary Table 1 ). Our previous study has reported a higher failure rate of sequencing metrics in samples with <25% malignant cells ( 7 ). These samples might allow detection of actionable mutations but need to be carefully considered for TMB estimation.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Sequencing sensitivity was therefore compromised, with few somatic coding mutations being detected (9 versus 51) and used in TMB scores (5 versus 24) compared to its paired slide ( Table 1 ; Supplementary Table 1 ). Our previous study has reported a higher failure rate of sequencing metrics in samples with <25% malignant cells ( 7 ). These samples might allow detection of actionable mutations but need to be carefully considered for TMB estimation.…”
Section: Resultsmentioning
confidence: 97%
“…Methods and data related to the microscopic estimation of tumour content on the Diff-Quik slide (involving estimating percent malignant cells to non-malignant cells, the approximate overall abundance of malignant cells and area of the glass slide covered by the smear), DNA extraction and sequencing by (TruSight Oncology 500 (TSO500 - Illumina)and the description of somatic mutations and TMB was previously reported ( 7 , 8 ). The sequence data was processed and analysed using the TruSight Oncology 500 Local App version 2.0 (Illumina), which estimates TMB using eligible variants/effective panel size (coding region with >50x coverage).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis pipeline of sequenced TSO500 libraries generates variant calls and also quality metrics for each sample and guideline quality thresholds. The use of TSO500 has been recently reported in non‐FFPE tissue, 20 however, studies aimed at comparing the performance of this type of materials to other FFPE materials generally preferred for NGS are still lacking in the academic literature, either regarding the yield of nucleic acid extractions or regarding the library quality metrics.…”
Section: Discussionmentioning
confidence: 99%
“… 30 A recent study assessed the feasibility of the TSO500 panel using Diff-Quick cytology smears from 27 patients with NSCLC, but sequencing failed in 5 cases (1 due to library preparation failure and 4 due to low median coverage). 31 …”
Section: Discussionmentioning
confidence: 99%